Social factors of willingness to share knowledge: in Relational Model Theory (RMT) / Norfadzilah Abd Razak, Faizuniah Pangil and Md Lazim Mohd Zin - Abd Razak, Norfadzilah; Pangil, Faizuniah; Mohd Zin, Md Lazim (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, Malaysia, 2018)
A willingness to share knowledge is an individual intention to share or not knowing. It is unenforceable but depends on individual’s itself. Recently, studies highlighted a social psychological context might be major factor that influences willingness to share knowledge. In sharing knowledge process, there is a need to have at least two actors as sender and recipient so that the sharing process will be effective. However, if the relationship between the two parties is harmful, the sharing process is not well implemented. Apart from this process, a social psychological vital stimulates individual’s intention and willingness to share knowledge. This study aimed to explore the fundamental of relational model theory, social factors and willingness to share knowledge. The finding will be discussed further the framework of relational model theory and willingness to share knowledge.